Race and Social Problems Restructuring Inequality - Bangs, Ralph; Davis, Larry E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
As much as Americans believe in the promise of an egalitarian, color-blind society, the reality is far from that ideal. People of color consistently lag behind their white counterparts in key quality-of-life areas. Despite many significant gains, widespread structural inequalities continue to exist--and thrive. Race and Social Problems takes the long view of this state of affairs, offering both multi-level analysis and a practical blueprint for social justice. It begins by explaining how race-related social problems have changed over the decades. This volume identifies factors contributing to their persistence in this century, most notably the central role of economic disparities in exacerbating related social problems and replicating them for future generations. The chapters expand on this knowledge by detailing innovative and successful strategies for addressing aspects of six major areas of inequality: Poverty: challenging standard American concepts of poverty. Education: approaches toward closing the achievement gap. Intergroup relations: enhancing race dialogues. Family and lifespan: programs targeting families, youth, and elderly. Criminal justice: reducing incarceration and increasing public safety. Health and mental health: promoting positive outcomes. Race and Social Problems casts a wide net across the most pressing social issues, clarifying both the immediate and larger tasks ahead for a range of professionals in such diverse fields as social work, anthropology, communications, criminology, economics, history, law, political science, psychology, public health, and sociology.
Part I: Introduction -- America's Racial Realities -- Do Current Race and Ethnicity Concepts Reflect a Changing America? -- Intergroup Dialogue: Race Still Matters -- Part II: Economics -- Wealth Building in Communities of Color -- Recent Employment Trends Among Black Men and Their Policy Implications -- Challenging the Conventional Understanding of American Poverty -- Part III: Education -- Interventions to Address Racial/Ethnic Disparities in School Discipline: Can Systems Reform be Race-Neutral? -- Exploring, Understanding and Closing the Achievement Gap(s): Efforts from Harlem to Homewood -- High School Quality and Race Differences in College Achievement -- Part IV: Special Topics: Family Matters: Strengthening the Fabric of Minority Families -- Aging and Health in Mexican Americans: Selected Findings from the Hispanic EPESE -- Racial Disproportionality in Prison -- Resetting Race -- Part V: Health: Disparities in Health Care for Minorities: An Ecological Perspective -- Considering the Role of Social Determinants of Health in Black-White Breast Cancer Disparities -- Understanding and Addressing Racial/Ethnic Disparities in Obesity -- Mental Health Indicators for African American Males.
Keywords: Psychology; Social work; Sociology; Personality; Social psychology; Psychology; Personality and Social Psychology; Social Work; Sociology, general; Electronic books